Warunki środowiskowe sprzyjające występowaniu trufli (Tuber spp.) na historycznych stanowiskach w Polsce - Rosa-Gruszecka, Aleksandra; Hilszczańska, Dorota; Szmidla, Hanna (Leśne Prace Badawcze, 2014)
This article highlights historical data regarding truffles’ occurrence in Poland. Along with the soil parameters the plant communities at the sites were studied. The results of the chemical soil analyses showed that the soil water pH at 5 sites was acidic (from 4.3 to 6.1), and only in one, Wiązowna, was the pH (7.2) conductive to truffle development. Similarly, the content of calcium carbonate (CaCO 3 ) in soil samples was low (from 0 to 0.03 %), except for Wiązowna, where CaCO 3 was 0.12 %. Among the 24 reported species of trees and shrubs, 7 species were host-plants of summer truffle ( Tuber aestivum Vitt.). Out of these 7 species, oak and hornbeam were present at four locations. Across the sites, 31 species of ground-layer plants were identified. Among these, Epipactis helleborine was only one host-species of summer truffle. Our findings indicate that the formation of truffle fruiting-bodies depends on specific habitat characteristics. The key factors determining this process are soil parameters, such as: texture, pH and calcium content. Our inventory showed that the sites we studied still persist as natural stands, although only one of them seems to be favorable for truffle development: this site is located in Wiązowna, where soil is of pH 7.2 and E. helleborine (host species for truffles from Orchidaceae) is found, fulfills the environmental requirements of truffles.